Dynamism and mechanism of digital currency (cryptocurrency) towards Islamic finance - Chowdhury, Mohammad Abdul Matin; Abdul Razak, Dzuljastri (Università Degli Studi di Torino, 2019)
Technology advanced has brought rapid changes in all human activities along with financial activities and tools. Digital currency one of the technological innovations which have taken significant focuses from consumers, investors, researchers, entrepreneurs and policy makers around the world. with the trend of changing patterns, Islamic finance is rapidly developing all over the world by serving Muslims and non-Muslims, as a result, it is mandatory for Islamic finance to adapt with modern technology systems in terms of providing innovative products and services to the consumers in line with shariah perspectives. As a result, cryptocurrency (digital currency) has taken the focus on Islamic scholars in regards of its permissibility. There are many arguments over the permissibility issues. Therefore, this study aims to explore those issues and mechanisms of cryptocurrency in order to evaluate with Islamic perspective. This study gathered secondary sources from past literatures, books, news and websites with qualitative approach. The findings inclined that there are still lacking in mechanisms of digital currency to comply with Islamic perspective such as real asset backed and legal authorization. The findings of this study will benefit the Islamic scholars and policy makers along with Muslim consumers and investors in regards of permissibility and developing existing cryptocurrency to widely use in the Islamic finance and banking sector.